Investigating HER2‐Low in Early Breast Cancer: Prognostic Implications and Age‐Related Prognostic Stratification - Endong Chen; Chen Chen; Yingying Chen; Jie You; Nan Chen; Shenlin Xu; Qingxuan Wang; Yefeng Cai; Xiaoqu Hu; Quan Li (Cancer Medicine)
ABSTRACT Background Recent studies about human epidermal growth factor receptor 2 (HER2)‐low values have garnered great interest among oncologists. We aimed to investigate whether HER2‐low impacts the prognosis of early‐stage breast cancer overall and in specific subgroups, explore differences in clinicopathologic markers, and examine the role of age in HER2‐low prognostic stratification. Materials & Methods We conducted a retrospective analysis of 6920 HER2‐negative breast cancer patients from the First Affiliated Hospital of Wenzhou Medical University (2010–2022). The study focused on the impact of HER2‐low status (immunohistochemistry +1 or +2, in situ hybridization not amplified) on overall survival (OS), considering the age at diagnosis. Results Generally, HER2‐low status correlated with less aggressive cancer indicators. No significant prognostic differences were observed between HER2‐low and HER2‐0 in the entire cohort, HR‐positive, and HR‐negative groups. However, in TNBC patients aged ≥ 65, HER2‐low correlated with significantly better OS (HR = 0.45, 95% CI 0.24–0.83, p = 0.011), a finding consistent after multivariable adjustment (HR = 0.34, 95% CI 0.14–0.80, p = 0.014). In other subgroups, prognosis did not significantly correlate with HER2 status. The combination of HER2‐low status and age plays a key role in prognostic stratification in TNBC. Patients aged ≥ 65 with HER2‐0 had considerably poorer prognoses compared to other subgroups. Conclusion This extensive retrospective study demonstrates that HER2‐low status cannot serve as an independent prognostic factor in the entire cohort, nor in the HR‐positive and HR‐negative groups individually. However, the combined factors of HER2‐low status and age may indicate a potential contribution to the prognostic stratification of TNBC.